PENGARUH MODEL PEMBELAJARAN SIMAYANG TIPE II BERBANTUAN MEDIA PhET TERHADAP HASIL BELAJAR DAN KEMAMPUAN REPRESENTASI VISUAL SISWA PADA MATERI LARUTAN ASAM BASA - Nenti Kurnia Wati; Rilia Iriani (Universitas Lambung Mangkurat, 2016)
Abstract. Studies have been conducted to determine the effect (1) the use of models of Simayang Type II PhET media aided the learning outcomes of students (2) the use of models of Simayang Type II PhET media aided visual representation of the ability of a solution of acids and bases. This research used quasy experimental design. The sample in this study is a class XI PMIA 2 as an experimental class and XI PMIA 3 as the control class. Experiments class using PhET media Simayang model with Type II consists of four phases, namely orientation, exploration imagination conceptual representation, internalization and evaluation. The results showed that (1) There are differences between the results of post-test experimental class and control class that is impact on learning outcomes (2) There are differences between the results of post-test experimental class and control class so that is influence on the ability of visual representation.Keywords: Simayang Type II, Learning Outcomes, Visual Representation Capabilities, Solutions Acid Base, Media PhET.